Review on the paper Reversed Crystal Growth - Pavel P. Fedorov (Pensoft Publishers, 2021)
Review on the paper Wuzong Zhou, Reversed Crystal Growth. Crystals. 2019; 9(1): 7 (16 pp). https://doi.org/10.3390/cryst9010007